2015 6th International Conference on Automation, Robotics and Applications (ICARA) 2015
DOI: 10.1109/icara.2015.7081176
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and selection of the Force Sensitive Resistors for gait characterisation

Abstract: Force Sensitive Resistors (FSRs) are used for kinetic evaluation of human gait by measuring under foot pressures during gait. FSRs from different manufacturers, with variation in morphologies and loading capacities were selected in past research projects. However a functional comparison of different FSRs and options on how to choose them for gait analysis is not established yet. In this work, investigation and comparison of behavioral patterns in measuring normal gait from two major FSR sensors are done. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The insole device developed in this study consists of three main components, as shown in Figure 1a. Firstly, five plantar force sensors (FSR-402, Interlink Electronics, Camarillo, CA, USA) are attached to the bottom of the insole sheet (S 1 -S 5 ) to receive the force exerted on the foot as you walk [14,15]. The sensor positions are shown in Figure 1b, though they change according to the shape of the wearer's foot.…”
Section: Hardware Descriptionmentioning
confidence: 99%
“…The insole device developed in this study consists of three main components, as shown in Figure 1a. Firstly, five plantar force sensors (FSR-402, Interlink Electronics, Camarillo, CA, USA) are attached to the bottom of the insole sheet (S 1 -S 5 ) to receive the force exerted on the foot as you walk [14,15]. The sensor positions are shown in Figure 1b, though they change according to the shape of the wearer's foot.…”
Section: Hardware Descriptionmentioning
confidence: 99%
“…Ozdemir and Barshan (2014) developed multi-sensor systems attached across the body to produce higher performance modules, but because of system complexity and discomfort it was impractical for everyday life. Shaikh et al (2015) investigated and compared behavioral patterns in measuring normal gait from two FSR sensors, FSR401 and FSR402, which led to FSR401 being termed as the optimum choice of sensor. Wu et al (2015) developed a wearable device using a single tri-axial accelerometer, which is placed on the user's waist but failed because of user's discomfort.…”
Section: Related Workmentioning
confidence: 99%
“…Their specified switching time delay was 1 ms. The FSR 406 sensor in Figure 4 [18] is more sensitive to forces with lower magnitude, being able to distinctively respond to forces as low as 20 g [19]. Considering cheap and reliable force sensor, it can be a suitable candidate to measure the force during interaction [17].…”
Section: System Configurationmentioning
confidence: 99%